Diagnosis of Cerebral Aneurysm Via Magnetic Resonance Angiography Screening: Emphasis on Legal Responsibility Increases False Positive Rate - Su-hee Cho; Ji-ye Lee; Kyeong-hwa Ryu; Dae Chul Suh (Neurointervention, 2018)
PurposeFalse positive diagnoses of cerebral aneurysm via magnetic resonance angiography (MRA) screening may increase unnecessary cerebral catheter angiography. The purpose of this study was to investigate the effects of medical liability on medical decision-making during radiologic interpretation.Materials and MethodsWe included 56 consecutive patients who were referred with suspected aneurysm based on MRA or computed tomography angiography (CTA) and showed no aneurysm on subsequent digital subtraction angiography (DSA). MRA and CTA were reviewed twice by two neuroradiology fellows who were blind as to whether the suspected lesions were true aneurysms or not. The second review was repeated after proposing that their decision was subject to legal liability and they would be responsible for medico-legal problems related to their diagnoses. Diagnostic differences based on each review were analyzed, focusing on changes in false positive diagnosis rates.ResultsA total of 63 suspected aneurysmal lesions detected via MRA or CTA were found to be negative based on DSA. At first review, 32 lesions were diagnosed as true aneurysms by observer 1 and 27 by observer 2, corresponding to false positive rates of 51% and 43% respectively. At the second review, 39 lesions (62%) were diagnosed by observer 1, and 30 (48%) by observer 2. Thus, there was an overall increase in false positive aneurysm diagnosis of 11% for observer 1 and 5% for observer 2, after emphasizing their responsibilities in the context of medical litigation.ConclusionConcerns about medical liability could result in increased false positive diagnoses of cerebral aneurysms via MRA screening. Whether repeated follow-up of the suspected lesion or catheter angiographic confirmation is better with regard to long-term patient outcomes requires further study.